Postnatal extra-embryonic tissues as a source of multiple cell types for regenerative medicine applications - Gubar, O.S.; Rodnichenko, A.E.; Vasyliev, R.G.; Zlatska, A.V.; Zubov, D.O. (Experimental Oncology, 2017)
Aim: We aimed to isolate and characterize the cell types which could be obtained from postnatal extra-embryonic tissues. Materials and Methods: Fresh tissues (no more than 12 h after delivery) were used for enzymatic or explants methods of cell isolation. Obtained cultures were further maintained at 5% oxygen. At P3 cell phenotype was assessed by fluorescence-activated cell sorting, population doubling time was calculated and the multilineage differentiation assay was performed. Results: We have isolated multiple cell types from postnatal tissues. Namely, placental mesenchymal stromal cells from placenta chorionic disc, chorionic membrane mesenchymal stromal cells (ChM-MSC) from free chorionic membrane, umbilical cord MSC (UC-MSC) from whole umbilical cord, human umbilical vein endothelial cells (HUVEC) from umbilical vein, amniotic epithelial cells (AEC) and amniotic MSC (AMSC) from amniotic membrane. All isolated cell types displayed high proliferation rate together with the typical MSC phenotype: CD73⁺CD90⁺CD105⁺CD146⁺CD166⁺CD34⁻CD45⁻HLA⁻DR⁻. HUVEC constitutively expressed key markers CD31 and CD309. Most MSC and AEC were capable of osteogenic and adipogenic differentiation. Conclusion: We have shown that a wide variety of cell types can be easily isolated from extra-embryonic tissues and expanded ex vivo for regenerative medicine applications. These cells possess typical MSC properties and can be considered an alternative for adult MSC obtained from bone marrow or fat, especially for allogeneic use.